(untitled) (Revista Sistemas de Producción Agroecológicos, 2020)
The sagu starch (Canna indica) performs importance for the Colombian agroindustry, nevertheless, the research on this one is small, and provoking that products like the bread of sagu still is not made in an industrial way. In addition, it’s very well known that the starches in his native structure present low efficiency during the industrial processes. Studies made with fermented starches of tapioca demonstrates that those starches present better characteristics for the agroindustrial processes in opposition to his native structure. For such a motive the present study of the starch was performed fermenting sagu (Canna indica) to observe the changes that the process generates in the starch of this plant in opposition to the native starch. For the study the starch was mixed with water in three different proportions from starch-water (1:2, 1:4 and 1:6) and bring under fermentation for 45 days. Samples of the starch was taken each five days (5, 10, 15, 20, 25, 30, 35, 40 and 45) in order to evaluate physicochemical, thermal and microbiological properties. It was determined that the relationship between the days of fermentation and the variables of acidity, humidity, density, ash content and particle size (less than 125 μm) is direct (Pearson correlation), that is, they are directly proportional. In contrast, the variables pH, gelatinization temperature and maximum viscosity have an inverse or negative relationship, that is, they decrease as the days of fermentation pass. Statistically it was verified that the relation starch: water used in the fermentation of the sago starch does not affect the mentioned variables. On the other hand, the results obtained from viscosity and gelatinization on days 40 and 45 of the 1:4 and 1:6 ratios are suitable for products such as jams, gelatins, mayonnaises, milk sweets and bakery products since they withstand temperatures up to 75.3°C and tend to increase the viscosity in the cooling stage, in addition to having low pH which helps to inhibit bacterial growth and high values of acidity that provides the characteristic taste of sagu starch. The existence of yeasts and amylolytic bacteria was demonstrated during fermentation. It should be noted that these starches are not suitable for all bakery applications, to select the type of bread that can be made with these starches an expansion test must be made.